Math virtual assistant

About Snapxam Calculators Topics Go Premium
ENGESP
Go!
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
d/dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

3x^2-2y^2-42x-4y+133=0

Solve the equation -4y+133+-42x+-2y^2+3x^2=0

Answer

$y_1=\frac{4+ \sqrt{336x+16}}{-4}\:\:,\:\:y_2=\frac{4- \sqrt{336x+16}}{-4}$

Step-by-step explanation

Problem

$3x^2-2y^2-42x-4y+133=0$
1

Subtract $133$ from both sides of the equation

$-4y-42x-2y^2+3x^2=-133$

Unlock this step-by-step solution!

Answer

$y_1=\frac{4+ \sqrt{336x+16}}{-4}\:\:,\:\:y_2=\frac{4- \sqrt{336x+16}}{-4}$

Struggling with math?

Access detailed step by step solutions to millions of problems, growing every day!